Foods of Spectacled Eiders Somateria fischeri in the Bering Sea, Alaska - Petersen, Margaret R; Piatt, John F; Trust, Kimberly A (Wildfowl, 1998)
The winter diet of Spectacled Eiders living in marine habitats is known only from two individuals described by Cottam (1939). Here we examine marine diets from 36 stomachs collected near St. Lawrence Island, Bering Sea, Alaska, during May-June in 1987 and 1992. All Spectacled Eiders ate Mollusca, including Gastropoda (snails; frequency of occurrence 20.0%; sole taxon 0.0%) and Bivalvia (bivalves; 80.0%; 48.0%), and Crustacea (barnacles, amphipods and crabs; 30.6%; 0.0%). One bird ate a cod. The predominant species group eaten was Macoma Clams (72.0%; 36.0%). Prey species of Spectacled Eiders occur predominantly in waters 25-60 m deep in the Bering Sea. To obtain these prey, especially the bivalves, on the winter area Spectacled Eiders must forage in waters exceeding 40 m. We speculate that Spectacled Eiders regularly forage at depths of 45-70 m throughout winter.